People Allocation Recommendation Engine - Nová, Denisa; Gála, Libor, 1965-; Mach, Michal; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2023)
This work includes an exploration of different approaches to developing a recommendation system and explores the automation solutions for people allocation available through the Salesforce App Exchange. The aim of this thesis is to develop a prototype of a recommender system that will help automate the people allocation process. This diploma thesis consists of the design and development of the prototype of the system. To develop it, the OpenUP methodology was followed. The entire solution is built on the Salesforce platform using Salesforce technologies. The resulting solution is then tested and evaluated based on predetermined requirements.
Vedoucí práce: Libor Gála
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: vývoj informačních systémů [obor dipl. práce]; diplomové práce; master's theses